STATUS SOSIODEMOGRAFI, STATUS GIZI, GAYA HIDUP, DAN KEBIASAAN MAKAN SEBAGAI FAKTOR TERKAIT HIPERTENSI DI KALIMANTAN - Ferdina, Ayunina Rizky; Setyawati, Budi; Fuada, Noviati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2023)
The prevalence of hypertension in Kalimantan, Indonesia, remains higher than the national average. This study aimed to examine the risk factors for hypertension that are relevant for people in the area. This observational study used a cross-sectional design using secondary data from the latest Basic Health Research (Riskesdas 2018). The dependent variable of this study is hypertension status, while the independent variables consist of sociodemographic status, nutritional status, health status and dietary habits. Multivariate logistic regression analysis was carried out to see the relationship of potential risk factors as independent variables with the subject's hypertension status. This research shows that 21.2% of non-pregnant adult subjects in Kalimantan have high blood pressure or hypertension. The results of statistical analysis show that significant risk factors for high blood pressure for this population include age, gender, education level, job category, smoking status, being an alcohol drinker, rarely consuming vegetables, frequently consuming grilled foods and instant seasonings, high Body Mass Index, and history of Diabetes Mellitus. Sociodemographic status as well as certain health status were found to be significant risk factors for hypertension in adults in Kalimantan. Only a few aspects of lifestyle and eating habits were identified as having a significant relationship with the incidence of hypertension.